A hálózatok emlékezetei, az emlékezetek hálózatai - O. Réti, Zsófia (Studia Litteraria, 2018)
The present paper aims to tentatively raise a number of issues regarding the complex relationship between collective memory and the internet, more specifically Web 2.0. First, I briefly demonstrate how the metaphors of the internet and of collective memory have shaped our understanding of the two topics, and I look at the possible interfaces between them. Then, capitalizing upon the metaphor of network, the most prevalent one of such ‘interfaces’, the paper seeks to explore the insights it can offer in relation with collective memories in the age of social media. Finally, I use the example of the late Kádár-era and its online memory to illuminate a few theoretical consequences of imagining contemporary online memory communities as networks.